2021
DOI: 10.1029/2021jb022084
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Rayleigh Wave Microseisms Constrained by Multiple Seismic Arrays

Abstract: Microseisms are the most energetic signals of Earth's ambient noise field. Locating the sources of microseisms helps us to understand arrivals on noise cross‐correlation functions (NCFs) and the asymmetric amplitude of Rayleigh waves on the positive and negative parts of the NCFs. Using a dense broadband seismic array in eastern China, we investigated temporal and spatial characteristics of Rayleigh wave microseisms in the frequency range of 45–155 mHz by conducting beamforming and Rayleigh wave amplitude‐azim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…With continued developments in seismic instrumentation, additional arrays of 3‐component, broadband seismometers have been emplaced across the globe during the last 30 years and have driven advances in understanding fault rupture dynamics (e.g., Ishii et al., 2005), improved resolution in seismic mantle imaging (e.g., Schmandt & Lin, 2014), and helped reveal the global source regions of ambient noise (e.g., Friedrich et al., 1998; Z. Wang et al., 2021). However, seismic arrays have been, and are today, overwhelmingly located in the northern hemisphere and long periods of operation are often required to both calibrate them and to attain maximal resolution in seismic imaging (Schweitzer et al., 2012).…”
Section: Future Opportunities and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…With continued developments in seismic instrumentation, additional arrays of 3‐component, broadband seismometers have been emplaced across the globe during the last 30 years and have driven advances in understanding fault rupture dynamics (e.g., Ishii et al., 2005), improved resolution in seismic mantle imaging (e.g., Schmandt & Lin, 2014), and helped reveal the global source regions of ambient noise (e.g., Friedrich et al., 1998; Z. Wang et al., 2021). However, seismic arrays have been, and are today, overwhelmingly located in the northern hemisphere and long periods of operation are often required to both calibrate them and to attain maximal resolution in seismic imaging (Schweitzer et al., 2012).…”
Section: Future Opportunities and Challengesmentioning
confidence: 99%
“…With continued developments in seismic instrumentation, additional arrays of 3-component, broadband seismometers have been emplaced across the globe during the last 30 years and have driven advances in understanding fault rupture dynamics (e.g., Ishii et al, 2005), improved resolution in seismic mantle imaging (e.g., Schmandt & Lin, 2014), and helped reveal the global source regions of ambient noise (e.g., Friedrich et al, 1998;Z. Wang et al, 2021).…”
Section: Broadband Arraysmentioning
confidence: 99%
“…In this study, we used waveform data of a temporary dense broadband array installed across the Weifang segment of the Tanlu Fault (hereinafter referred to as TLarray). The array was deployed between August of 2017 and July of 2018 and comprised 31 Nanometrics trillium 120 posthole sensors and centaur digitizers with a station spacing of ∼5–30 km (Wang et al., 2021). We also used data from another linear array with 51 broadband stations in the southern part of the study area.…”
Section: Datamentioning
confidence: 99%
“…(2020) derived the sources of SFMs possibly dwell over wide areas of the Atlantic Ocean where the water depth may be up to 2,000 m based on NCFs of data recorded from the east coast of America; and Wang et al. (2021) identified a total of five SFMs sources including the deep ocean area in Southern ocean and northern Pacific ocean. In addition, direct observations on ocean bottom seismometers (OBSs) also clearly detected SFMs in deep ocean (e.g., Guo, Xue, et al., 2020; Stephen et al., 2003; Tian & Ritzwoller, 2015; Yang et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While shallow water are well accepted source regions for SFMs, a few studies located the sources of SFMs observed in deep ocean: for example, Stehly et al (2006) located the sources of SFMs in the northern Atlantic and northern Pacific during the winter and in the Indian Ocean and southern Pacific during the summer by analyzing data recorded in eastern United States, Europe and Tanzania; Retailleau et al (2017) located the sources of SFMs in both shallow and deep water in the northern Atlantic Ocean by utilizing spurious arrivals based on noise correlation functions (NCFs); derived the sources of SFMs possibly dwell over wide areas of the Atlantic Ocean where the water depth may be up to 2,000 m based on NCFs of data recorded from the east coast of America; and Wang et al (2021) identified a total of five SFMs sources including the deep ocean area in Southern ocean and northern Pacific ocean. In addition, direct observations on ocean bottom seismometers (OBSs) also clearly detected SFMs in deep ocean (e.g., Stephen et al, 2003;Tian & Ritzwoller, 2015;Yang et al, 2012).…”
mentioning
confidence: 99%